Overcoming the Challenges of Vocational Education in Indonesian SMK: Ideas on Curriculum Improvement, Teaching Quality, And English Language Teaching - Aryawan, Fatah Nasikh (Journal of Practice Learning and Educational Development, 2023)
Vocational education in Vocational High Schools (SMK) plays an important role in preparing students for the world of work. In contrast to general education, vocational education in SMK aims to develop practical skills that are in line with industry needs and provide students with a strong foundation to enter the workforce after graduation. SMKs have a strategic role in supporting a country's economic growth. Through vocational education programs, SMKs can prepare a skilled and ready-to-use workforce to meet industry needs. By combining theory and practice, vocational education in SMK can provide students with relevant skills and abilities needed in the work environment. However, vocational education in SMK also faces various challenges that need to be addressed. These challenges relate to curriculum, teaching quality, and English language teaching. This article aims to analyze and present the challenges faced in improving the curriculum to keep up with the industry. In addition, the quality of teaching is an important aspect that needs to be considered so that students can get a quality education. Furthermore, English language teaching is also the focus of this article, given the importance of English language skills in facing global challenges. In addition to discussing the challenges, this article will also propose possible solutions that can be implemented to overcome these problems. These solutions may include improving the curriculum, enhancing the quality of teaching through teacher training and professional development, as well as more effective strategies in teaching English in SMK.